(untitled) (Fiep Bulletin - online, 2012)
Objectives: To evaluate the clinical and transport conditions of newborns admitted in public neonatal intensive care units in João Pessoa – PB. Methods: Documental research, retrospective, which comprehended the analysis of 36 medical registers of newborns admitted in Intensive Care Units after transport in 2008, 2009 and in the first quarter of 2010. The descriptive analysis of data was done from the absolute and percent frequency, and from the correlation among the evaluated variables. Results: From the transported newborns (61.5%) were born by eutocic delivery. The sex was notified in 97.2% of medical registers and, from these, 65.7% were masculine and 34.3% were feminine. 78.8% of newborns were admitted in the first 24 hours after birth. The prematurity and respiratory disturbances associated to other alterations constituted the main causes of indicating inter-hospital transport in all the years of study. The precedence of newborns was registered in 97.2% of the sample: 50% of them were from the littoral region, 19.4% from brejo paraibano, 16.7% from sertaneja region, and 11.4% from Pernambuco State. It was evidenced that only 2.8% of transports were accompanied by a complete transport team. Conclusions: The conditions of transport did not obey the recommendations of the Ordinance nº 824/GM. We can consider that the inexistence of protocols of transport and admission of newborns can have influenced the underreporting of information related to their clinical conditions, which are very important to the continuity of care and whose underreporting can provoke serious risks to newborns that need to be transferred to reference services.